Reflections on the Concept of Political Culture and Historical Research on Democracy in Latin - Rodríguez Franco, Adriana (Universidad Pedagógica y Tecnológica de Colombia, 2017)
The objective of this article is to reflect on the concept of political culture as a fundamental analytical tool for studies in political history and specifically historiography. In the last two decades, this concept has been used for the study of the establishment and development of democracy in Latin America. The present text will focus on the movement of this category from Political Science to History, and the way in which it has been adapted to the needs of the historical interpretation of Western and Latin American political realities. This movement has not been exempt from questioning and debates; nevertheless it has been a key factor in the renovation of historiographic studies on political issues, particularly related with the positioning of democracy as an object of study in Latin American historiography.